Conceptual Integration in Online Interdisciplinary Study: Current Perspective, Theories, and Implications for Future Research - Morrison, James L. (International Review of Research in Open and Distributed Learning, 2003)
The University of Oklahoma's College of Liberal Studies was established as an academic unit in 1960, and provides interdisciplinary education to non-traditional students with programs for Bachelor’s and Master’s degrees in Liberal Studies. In the Fall of 2003, the College offered both degrees in a fully online format, with no student residency requirements. Learners engaged in interdisciplinary studies online are faced with the difficult task of integrating chaotic pieces of information, various ways of knowing, and dissimilar concepts from various disciplines into a coherent and integrated body of knowledge. The purpose of this paper is to discuss the phenomenon of conceptual integration, and the unique challenges and opportunities of providing interdisciplinary study online in the context of conceptual integration.